2018
DOI: 10.5897/ajar2016.12050
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency and yield gap of smallholder wheat producers in Ethiopia: A Stochastic Frontier Analysis

Abstract: Improving technical efficiency of smallholder farmers is one of the options to increase wheat yield in developing countries. This paper assesses technical efficiency, factors for inefficiency and the yield gap due to technical inefficiency in major wheat producing regions of Ethiopia, where the support to agricultural research for development of strategic crops (SARD-SC) wheat project has been implemented using primary data collected from 946 sample households operating 1616 wheat plots. One-step stochastic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…This agrees with a report by Tadele et al. (2018) in Ethiopia. The study revealed that income from farm activities significantly and negatively influences major crops, wheat, and teff production inefficiency.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This agrees with a report by Tadele et al. (2018) in Ethiopia. The study revealed that income from farm activities significantly and negatively influences major crops, wheat, and teff production inefficiency.…”
Section: Resultssupporting
confidence: 94%
“…Secondly, households with a greater number of livestock holding may easily supply oxen draught power for plowing and threshing as a source of labor, and organic fertilizer mainly from their excreta. This agrees with a report by Tadele et al (2018) in Ethiopia. The study revealed that income from farm activities significantly and negatively influences major crops, wheat, and teff production ineffi- ciency.…”
Section: Climate Change Adaptation Practices and Crop Production Inef...supporting
confidence: 93%
“…Waterlogging-induced partial stomatal closure could constrain internal CO 2 levels and limit carbon fixation (Malik et al, 2001; Striker et al, 2005), but this variable has rarely been quantified (e.g., in wheat, Wu et al, 2014; in rapeseed, Leul and Zhou, 1998). Apart from stomatal limitations, photosynthesis rates can also be determined by non-stomatal factors, such as mesophyll conductance (Jones, 1985; Flexas and Medrano, 2002), damage to photosystem II (PSII) caused by reactive oxygen species (ROS) (Nishiyama et al, 2006; Ashraf, 2012), and leaf chlorosis related to chlorophyll degradation due to an accelerated leaf senescence (Hörtensteiner, 2006; Araki et al, 2012). Although there are reports regarding the impact of waterlogging on carbon fixation of the winter crops in this study (e.g., Huang et al, 1994 for wheat; Pang et al, 2004 for barley; Leul and Zhou, 1998 for rapeseed, and Malik et al, 2015 for field pea), comparisons between these species are scarce (see de San Celedonio et al, 2017 for wheat and barley).…”
Section: Introductionmentioning
confidence: 99%